Risk assessment of non-point source pollution in tropical watersheds considering water functional zones - Shiyu Xue; Yanhu He; Hao Cai; Jun Li; Lirong Zhu; Changqing Ye (Ecological Indicators)
A comprehensive assessment of the spatiotemporal characteristics of non-point source (NPS) pollution risk in watersheds is essential for effective water pollution management. However, few studies comprehensively assess the risk of land-based and water-based NPS pollutant loads in tropical watersheds characterized by distinct wet and dry seasons. Therefore, this study employs the Soil and Water Assessment Tool (SWAT) model and integrates the concept of water function zones (WFZ) to comprehensively assess the spatiotemporal characteristics, source apportionment, and wet and dry season-specific risk of NPS pollution in the Wanquan River Basin (WRB), considering both the land surface loading risk and the input risk from adjacent water bodies. The research findings indicate that the risk of NPS pollution demonstrates significant seasonal and spatial variability. In terms of spatial distribution, the high-load areas of total nitrogen (TN) and total phosphorus (TP) from NPS are primarily concentrated in downstream regions characterized by extensive agricultural land and orchards. In terms of temporal distribution, the risk of NPS pollution from ammonia nitrogen (NH3-N), TN, and TP increased by 26.68%, 58.70%, and 21.05%, respectively, during the wet season (May − October) compared to the dry season (November − April). Furthermore, there is no significant positive correlation between the risk of NPS pollution and the corresponding land-based NPS pollution load. The risk of NPS pollution is significantly influenced by pollutant inputs from adjacent water bodies. Regions characterized by high land-based NPS pollutant loads do not necessarily correspond to high NPS risk, and conversely, regions with high NPS risk do not necessarily exhibit high land-based NPS pollutant loads. The research findings provide a valuable reference for the precise risk assessment and effective management of NPS pollution in watersheds.